President's Message - Mushayandebvu, Barbara (Operating Room Nurses Association of Canada Journal, 2019)
Where does time go? Two years ago I embarked on this journey as ORNAC’s President with you. And now I have completed my term. In 2017 I outlined my commitments to you, the ORNAC membership, and now I would like to report on what has been accomplished: